Evil Children in the Popular Imagination - Renner, Karen J.; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
Focusing on narratives with supernatural components, Karen J. Renner argues that the recent proliferation of stories about evil children demonstrates not a declining faith in the innocence of childhood but a desire to preserve its purity. From novels to music videos, photography to video games, the evil child haunts a range of texts and comes in a variety of forms, including changelings, ferals, and monstrous newborns. In this book, Renner illustrates how each subtype offers a different explanation for the problem of the "evil" child and adapts to changing historical circumstances and ideologies.
Acknowledgements -- Introduction -- 1. Monstrous Births -- 2. Gifted Children -- 3. Child Ghosts -- 4. Possessed Children -- 5. Ferals -- 6. Changelings -- Primary Sources -- Works Cited -- Index.
Keywords: Youth-Social life and customs; Film genres; Comparative literature; Youth Culture; Childhood, Adolescence and Society; Media and Communication; Comparative Literature